Age structure and multi-model growth estimation of longnose stingray Hypanus guttatus (Dasyatidae: Myliobatoidei) from north-east Brazil - Gianeti, Michel D.; Santana, Francisco M.; Yokota, Leandro [UNESP]; Vasconcelos, Jonas E.; Dias, June F.; Lessa, Rosangela P. (Wiley, 2019)
We collected 729 Hypanus guttatus from the northern coast of the state of Rio Grande do Norte (RN), of which 196 were used to estimate age and growth. Ninety-five were male (12.7 to 57.0 cm disc width; W D ) and 101 were female (13.0 to 88.5 cm W D ); females were significantly larger than males. Cross sections of vertebrae showed band-pairs ranging from 0 to > 14 in females and from 0 to 9 in males. New-borns presented an opaque edge at birth in vertebrae without a birthmark. The average percentage of error (APE; %E) for the entire sample provided evidence that ages were repeatable. The mean monthly marginal increment (I M ) indicates annual band-pair formation from August to November. The annual cycle model for one band-pair deposition provided the best fit to data based on the AIC, with peaks between August and October, similar to that found in the I M analysis, suggesting an annual formation pattern. A multi-model approach that included four models based on the observed mean W D at age indicated a modified von Bertalanffy growth model as the best for describing the species growth: W 0 (W D at birth) = 14.6 cm for both sexes; females W ∞ = 98.61 cm (95% CI = 87.34–114.61 cm); k = 0.112 year −1 (CI = 0.086–0.148 year −1 ); males W ∞ = 60.22 cm (CI = 55.66–65.35 cm); k = 0.219 year −1 (CI = 0.185–0.276 year −1 ). The age-at-maturity in males and females is 5 years and 7 years, respectively. The age composition shows that most (84%) specimens were aged 0 to 2 years. The information provided here is essential for analytical assessments of H. guttatus, which is subject to significant fishing pressure mainly on new-borns and juveniles.
Keywords: age and growth; age structure; Dasyatis guttata; longnose stingray; north-east Brazil